Tinjauan Desain Karakter Komik Mice terhadap Kesesuaian Karakter Indonesia - Hasian, Irene; Utami, Anissa Jiwojati (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Media Komunikasi Trisakti, 2018)
The increase in popularity of Indonesian comics happens after many print and webcomic presence comics as a medium of communication between the author with the reader. Growth of Indonesian comic starts as expression media of authorâ€™s frustration about Indonesian politic and nowadays comic as a sliceâ€ofâ€life comic or in order to tell certain situation. Cartoonist Muhammad Misrad commonly called Mice is a comic artist who is already struggling in the comic world for a dozen years and successfully communicating the Indonesian people's lives and many people call it as soâ€ Indonesian comic. The character by Mice is perceived by writer as a soâ€Indonesian character. This reinforces the author desire to examine the character of Mice comic and the suitability with Indonesian character. The method used in this research is a qualitative approach. The explanation of the research methods for the required data will be divided into several different sub chapters. Phases of the research starting from data collection, sampling process, analyzing process, to conclusion. The writer uses a sample based on the comic book that tells the story of Indonesia people daily life from 2011 to 2015 as many as two samples of comic books. The analysis focuses on the visual character that covers the body shape, manner of dress, facial expressions and body gestures. The conclusions drawn by the overall visual analysis of the characters in the comic as well as compliance with reality.